Fostering 21st century digital literacy and technical competency - Cartelli, Antonio, 1954- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2013)
"This book offers the latest in research on the technological advances on computer proficiency in the educational system and society, bringing together theories and experiences in order to create a common framework"--Provided by publisher.